Adolescents Scientific Understanding of Reproductive Health - Wijayanti, Urip Tri (Proceeding International Conference on Religion, Science and Education, 2025)
Adolescents have an important role in shaping the future of a country. In reality, adolescents cannot avoid risky behavior. In North Sulawesi Province, based on the results of SKAP 2019, as many as 4.8 percent of adolescents have been involved in premarital sexual relations. This study aims to identify adolescents’ knowledge about women’s fertile period. This research is a quantitative study that applies a cross-sectional design and utilizes secondary data from the 2019 Program Accountability Performance Survey (SKAP) of North Sulawesi Province. Respondents in this study were unmarried adolescents aged 10-24 years. The results of the enumeration obtained 988 adolescents, with details of 546 men and the remaining 442 women. The dependent variable was the knowledge of adolescents about the female fertile period, the independent variables were age, residence and education. Variables were analyzed univariately and bivariate. The results showed that in general, adolescents in North Sulawesi province did not have good knowledge about the fertile period in women. Female adolescents have a higher percentage of knowledge about the fertile period of women than male adolescents, then the higher the age of men the better the knowledge about the fertile period of women. By region, adolescents in urban areas, both male and female, have higher knowledge about fertile period than those in rural areas. Finally, at the education level, male and female adolescents at the elementary and junior high school education levels had lower knowledge about the fertile period in women compared to high school and college education. The recommendation is to increase education about female childbearing period widely among adolescents and improve accessibility to health services in rural adolescents with high school education and below.